Widely Project: Utilizing an Ultra-Wide Angle Lens in Photographing Museum Bahari Jakarta - Alyatalatthaf, Muhammad Dicka Ma'arief (Rekam, 2024)
An ultra-wide angle lens is an “abnormal” type of lens that is capable of capturing scenes with a super vast perspective. The strongest characteristic of this lens is its distortion. Often distortions are seen as imperfections and disasters. However, in the “Widely Project”, distortion is used to create a unique and aesthetic perspective. The aim of this research is to use an ultra-wide angle lens to photograph Museum Bahari Jakarta. The photography project was subsequently utilized to preserve objects in the museum and the architecture of its buildings, which contain the historical story of the archipelago. The results show that ultra-wide angle lens are able to: create an attractive, artistic, and aesthetic perception, a “real” feeling on miniatures, furthermore a majestic atmosphere on ships and buildings.